2007
DOI: 10.1007/bf03033990
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of upright position imaging with medium-energy collimator for sentinel node lymphoscintigraphy in breast cancer patients

Abstract: Objective: To evaluate the advantage of upright position imaging with a medium-energy collimator for the detection of sentinel lymph node (SLN). Methods: Thirty-four patients with operable breast cancer underwent sentinel node lymphoscintigraphy with 99m Tc-tin colloid. Images were obtained in 5 different positions and paired images from the same patient were compared using side-by-side interpretation. Images were compared in 3 groups: group 1 (anterior view); supine (SAV) vs. upright (UAV), group 2 (oblique v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 9 publications
(19 reference statements)
1
14
0
Order By: Relevance
“…Tsushima et al [16] reported the appearance of star-shaped artifacts caused by septal γ-ray penetration, which could impair the visualization of SLNs located near the tumor. Based on this report, the routine imaging in authorial institution is using a LEGP with a thick septal to suppress the appearance of artifacts.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…Tsushima et al [16] reported the appearance of star-shaped artifacts caused by septal γ-ray penetration, which could impair the visualization of SLNs located near the tumor. Based on this report, the routine imaging in authorial institution is using a LEGP with a thick septal to suppress the appearance of artifacts.…”
Section: Figurementioning
confidence: 99%
“…For example, several papers [8][9][10][11][12] reported that modifying the imaging position improved the accuracy of SLN detection. As these methods increased the distance between the C region and axilla by modifying the imaging position, scattering from the injection site could be avoided.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…SPECT CT improves pre-operative localisation of draining nodes by detecting nodes missed by planar imaging, excluding non-nodal false positive sites of uptake and accurately localising axillary and extra-axillary nodes particularly in those who are overweight [55,56] . Upright imaging may also be advantageous [57] . Recent work has also shown the potential of the portable gamma camera in theatre over the hand-held probe [58] .…”
Section: Technical Issuesmentioning
confidence: 99%